High-contrast reversible multiple color-tunable solid luminescent ionic polymers for dynamic multilevel anti-counterfeiting. Issue 1 (29th October 2022) - Ma, Xiao; Zhou, Mingyue; Jia, Ling; Ling, Guangkun; Li, Jiashu; Huang, Wei; Wu, Dayu
Abstract : Ionic polymers obtained by grafting charged AIE-active chromophores achieve rare high-contrast reversible multiple color-tunable emission in response to different solvent stimuli, possessing huge potential applications in dynamic anti-counterfeiting. Abstract : Dynamic color-tunable luminescent materials, which possess huge potential applications in advanced multilevel luminescence anti-counterfeiting, are of considerable interest. However, it remains challenging to develop simple high-contrast reversible multiple (triple or more than triple) color-tunable high-efficiency solid luminescent materials with low cost, facile synthesis, and good processability. Herein, by simply grafting charged multi-color AIEgen-based chromophores into polymers, a series of high-efficiency multiple color-tunable luminescent single ionic polymers are constructed through tuning feed ratios, counter anions and reaction solvents. Remarkably, some ionic polymers can not only achieve rare high-contrast reversible multiple color-tunable emission in solid states in response to different solvent stimuli, but also could realize excitation-dependent color-tunable emission. To the best of our knowledge, such charming multiple (triple or more than triple) color-tunable solid polymers responding to multiple external stimuli are still rare. Based on comparative studies of emission spectra, excitation spectra and fluorescence lifetimes before and after swelling, it could be inferred that solvent stimuli could induce microstructure changes of these ionic polymers and then change the aggregated-states of their corresponding AIE-active emission centers. Moreover, the different solvent stimuli could induce to produce different degrees of microstructure changes, resulting in their unique multiple color-tunable emission. More significantly, these smart color-tunable ionic polymers show great promise for applications in dynamic multilevel (three-level or even more than three-level) anti-counterfeiting.